Cognition and culture : a cross-cultural approach to cognitive psychology - Altarriba, Jeanette, 1964- (Advances in psychology (Amsterdam, Netherlands), 1993)
While the main source of knowledge of human cognition has come from studies of information processing in a single culture, primarily within the U.S. or within certain countries in Europe, much research has also been conducted in other parts of the world. Can the study of cognition across cultures lead us to interesting conclusions about human cognition in general? Surely any general theory of language processing, for example, must be able to explain phenomena observed across cultures and not just within a single one. This book is an attempt to look at this issue of universals in thinking and understanding by providing a compendium of cross cultural investigations in the four major areas of cognitive psychology: (1) memory and knowledge representation, (2) language processing, (3) perception, and (4) reasoning and problem solving. The differences found across cultures are also fascinating and extremely informative. A final chapter provides a summary of the major findings reported in each of these areas. The chapters included in this work were written for those interested in cross-cultural psychology and also those with an interest in cultural anthropology. The authors are well-known in the areas of cross-cultural psychology, cognitive psychology, linguistics, and anthropology. However, the reader need not be an expert in any one of these fields to understand the conclusions and implications of the work reported here.